Beginning Java and Flex : migrating Java, Spring, Hibernate, and Maven developers to Adobe Flex - Di Pisa, Filippo (Expert's voice in Web development., 2009)
"Learn to build powerful enterprise Java applications using Adobe Flash as the presentation layer"--Cover.